Design, synthesis and in vivo evaluation of 3-arylcoumarin derivatives of rhenium(I) tricarbonyl complexes as potent antibacterial agents against methicillin-resistant Staphylococcus aureus (MRSA) - Sovari, Sara Nasiri; Vojnovic, Sandra; Bogojevic, Sanja Skaro; Crochet, Aurelien; Pavic, Aleksandar; Nikodinovic-Runic, Jasmina; Zobi, Fabio (European journal of medicinal chemistry, 2020)
We have prepared a series of ten 3-arylcoumarin molecules, their respective fac-[Re(CO)3(bpy)L]+ and fac-[Re(CO)3(L⁀L)Br] complexes and tested all compounds for their antimicrobial efficacy. Whereas the 3-arylcoumarin ligands are virtually inactive against the human-associated pathogens with minimum inhibitory concentrations (MICs) > 150 μM, when coordinated to the fac-[Re(CO)3]+ core, most of the resulting complexes showed remarkable antibacterial potency. Several rhenium complexes exhibit activity in nanomolar concentrations against Gram-positive pathogens such as Staphylococcus aureus strains, including methicillin-resistant S. aureus (MRSA) and Enterococcus faecium. The molecules do not affect bacterial cell membrane potential, but some of the most potent complexes strongly interact with DNA, indicating it as a possible target for their mode of action. In vivo studies in the zebrafish model showed that the complexes with anti-staphylococcal/MRSA activity were non-toxic to the organism even at much higher doses of the corresponding MICs. In the zebrafish-MRSA infection model, the complexes increased the survival rate of infected fish up to 100% and markedly reduced bacterial burden. Moreover, all rescued fish developed normally following the treatments with the metallic compounds. [Display omitted] •3-arylcoumarin derivatives of rhenium with antimicrobial properties.•Active complexes against S. aureus and E. faecium in nanomolar concentrations.•DNA interaction possible mode of activity.•Complexes efficient in the zebrafish-MRSA infection model.